First description of the male of Notiocoelotes pseudolingulatus (Araneae: Agelenidae) from Hainan Island, China - Han, Guang-Xin; Zhang, Feng; Zhang, Zhi-Sheng (Zootaxa, 2011)
The genus Notiocoelotes was established by Wang, Xu & Li, 2008. At present, it includes 11 species (Platnick 2011), all from Southeast Asia: China (Hainan Island), Laos, Thailand and Vietnam (Wang, Xu & Li, 2008; Liu & Li, 2010). While studying the Notiocoelotes species collected from Hainan Island, China, we found one male and two female Notiocoelotes specimens in the same locality. We identified the female as Notiocoelotes pseudolingulatus Liu & Li, 2010. The male specimen has habitus and markings very similar to the female of N. pseudolingulatus, and the characters of palpal organ conform to the genus Notiocoelotes. We therefore identified it as the male of N. pseudolingulatus, and describe it here. The format of the description and abbreviations of morphological terms follow that of Wang, Xu & Li, 2008.